Answer:
![\frac{(x-2)^2}{9}+\frac{(y-1)^2}{16}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-2%29%5E2%7D%7B9%7D%2B%5Cfrac%7B%28y-1%29%5E2%7D%7B16%7D%3D1)
Step-by-step explanation:
![x=2-3\cos(t)](https://tex.z-dn.net/?f=x%3D2-3%5Ccos%28t%29)
![y=1+4\sin(t)](https://tex.z-dn.net/?f=y%3D1%2B4%5Csin%28t%29)
Let's solve for
in the first equation and then solve for
in the second equation.
I will then use the following identity to get right of the parameter,
:
(Pythagorean Identity).
Let's begin with
.
Subtract 2 on both sides:
![x-2=-3\cos(t)](https://tex.z-dn.net/?f=x-2%3D-3%5Ccos%28t%29)
Divide both sides by -3:
![\frac{x-2}{-3}=\cos(t)](https://tex.z-dn.net/?f=%5Cfrac%7Bx-2%7D%7B-3%7D%3D%5Ccos%28t%29)
Now time for the second equation,
.
Subtract 1 on both sides:
![y-1=4\sin(t)](https://tex.z-dn.net/?f=y-1%3D4%5Csin%28t%29)
Divide both sides by 4:
![\frac{y-1}{4}=\sin(t)](https://tex.z-dn.net/?f=%5Cfrac%7By-1%7D%7B4%7D%3D%5Csin%28t%29)
Now let's plug it into our Pythagorean Identity:
![\cos^2(t)+\sin^2(t)=1](https://tex.z-dn.net/?f=%5Ccos%5E2%28t%29%2B%5Csin%5E2%28t%29%3D1)
![\frac{x-2}{-3})^2+(\frac{y-1}{4})^2=1](https://tex.z-dn.net/?f=%5Cfrac%7Bx-2%7D%7B-3%7D%29%5E2%2B%28%5Cfrac%7By-1%7D%7B4%7D%29%5E2%3D1)
![\frac{(x-2)^2}{(-3)^2}+\frac{(y-1)^2}{4^2}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-2%29%5E2%7D%7B%28-3%29%5E2%7D%2B%5Cfrac%7B%28y-1%29%5E2%7D%7B4%5E2%7D%3D1)
![\frac{(x-2)^2}{9}+\frac{(y-1)^2}{16}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-2%29%5E2%7D%7B9%7D%2B%5Cfrac%7B%28y-1%29%5E2%7D%7B16%7D%3D1)
Answer:
I'm not very sure about this one what icing in probably not going to be right but what I think is that they're not the same because look at the size difference imagine putting an adult's next to a baby that's kind of what it's like the bigger quadrilateral is also the adults while the little one is the baby what do you think about that I probably think that they're not saying
Step-by-step explanation:
sorry I gave it to you in my answer
Answer would be C
Because I always use the rule of :
B - Brackets
I - indices
D - division
M - multiplication
A - addition
S - subtraction
The expressions have the same expansion I'd say because the pairs 2 and 30, 3 and 20, and 4 and 15 because they are all equivalent to 60 because they are all factors of 60.
Same goes with the other pairs, because they are all equivalent to 48 because they are all factors of 48.